2007
DOI: 10.1038/sj.bjc.6603675
|View full text |Cite
|
Sign up to set email alerts
|

Target gene selectivity of hypoxia-inducible factor-α in renal cancer cells is conveyed by post-DNA-binding mechanisms

Abstract: Inactivation of the von Hippel -Lindau tumour suppressor in renal cell carcinoma (RCC) leads to failure of proteolytic regulation of the a subunits of hypoxia-inducible factor (HIF), constitutive upregulation of the HIF complex, and overexpression of HIF target genes. However, recent studies have indicated that in this setting, upregulation of the closely related HIF-a isoforms, HIF-1a and HIF-2a, have contrasting effects on tumour growth, and activate distinct sets of target genes. To pursue these findings, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 35 publications
9
100
0
Order By: Relevance
“…HIF-2a is associated with luminal breast cancer DP Stiehl et al target genes Lau et al, 2007), further supported by the fact that the DNA-binding basic helixloop-helix as well as the Per-ARNT-Sim domains are 487% conserved between both transcription factors. We constructed HIF-1a/HIF-2a hybrid expression plasmids (designated H1a/H2a and H2a/H1a, respectively) with interchanged basic helix-loop-helix and Per-ARNT-Sim portions as schematically depicted in Figure 5d.…”
Section: Immunohistochemical Analyses Of Ca9 and Glut1mentioning
confidence: 94%
See 1 more Smart Citation
“…HIF-2a is associated with luminal breast cancer DP Stiehl et al target genes Lau et al, 2007), further supported by the fact that the DNA-binding basic helixloop-helix as well as the Per-ARNT-Sim domains are 487% conserved between both transcription factors. We constructed HIF-1a/HIF-2a hybrid expression plasmids (designated H1a/H2a and H2a/H1a, respectively) with interchanged basic helix-loop-helix and Per-ARNT-Sim portions as schematically depicted in Figure 5d.…”
Section: Immunohistochemical Analyses Of Ca9 and Glut1mentioning
confidence: 94%
“…However, expression analyses in a renal clear cell carcinoma-derived cell line deficient for HIF-1a revealed preserved hypoxic induction of many known HIF target genes, indicating that effectively both HIF-a isoforms contribute to hypoxia-induced transcription (Hu et al, 2003). Domain-swapping experiments between HIF-1a and HIF-2a provided experimental evidence for the interchangeability of the DNA-binding regions of either isoform and attributed gene selectivity to the N-terminal transactivation domains of HIF-a Lau et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…By swapping protein domains between HIF1α and HIF2α, several groups demonstrated that this transcriptional specificity resided in the N-terminal activation domain (N-TAO), suggesting that differential interactions with transcriptional co-factors likely determine differential gene activation 29,30 . Recently, multiple groups have used chromatin immunoprecipitation coupled to tiled microarrays (ChiP-chip) to assess HIFα binding across the genome 31-35 .…”
Section: Direct Regulation Of Gene Expression By Hif1α and Hif2αmentioning
confidence: 99%
“…Both HIF-a subunits can bind to the endogenous HREs of hypoxiaresponsive genes; however, binding is not sufficient for target gene activation. 35,36 In contrast, C-terminal regions of each protein are required for specificity. For select targets, the N-TAD is sufficient to confer target gene specificity and replacement of the HIF-2a N-TAD with the analogous region of HIF-1a switches the specificity of these proteins.…”
Section: Transcriptional Targetsmentioning
confidence: 99%
“…36 In contrast, targets such as prolyl hydroxylase-3 (PHD3) require additional regions of the HIF-2a protein to be induced. 35 Cooperation with other transcription factors may also be required for maximal and cell-type-specific upregulation of HIF target genes ( Figure 2). Multiple Ets family transcription factors can cooperate with HIF-2a for hypoxic gene induction.…”
Section: Transcriptional Targetsmentioning
confidence: 99%